Computationally Empowered Workflow Identifies Novel Covalent Allosteric Binders for KRASG12C. (1st April 2020) - Mortier, Jérémie; Friberg, Anders; Badock, Volker; Moosmayer, Dieter; Schroeder, Jens; Steigemann, Patrick; Siegel, Franziska; Gradl, Stefan; Bauser, Marcus; Hillig, Roman C.; Briem, Hans; Eis, Knut; et al.
Abstract: Due to its frequent mutations in multiple lethal cancers, KRAS is one of the most‐studied anticancer targets nowadays. Since the discovery of the druggable allosteric binding site containing a G12C mutation, KRAS G12C has been the focus of attention in oncology research. We report here a computationally driven approach aimed at identifying novel and selective KRAS G12C covalent inhibitors. The workflow involved initial enumeration of virtual molecules tailored for the KRAS allosteric binding site. Tools such as pharmacophore modeling, docking, and free‐energy perturbations were deployed to prioritize the compounds with the best profiles. The synthesized naphthyridinone scaffold showed the ability to react with G12C and inhibit KRAS G12C . Analogues were prepared to establish structure‐activity relationships, while molecular dynamics simulations and crystallization of the inhibitor‐KRAS G12C complex highlighted an unprecedented binding mode. Abstract : Discovery of a novel covalent KRAS G12C inhibitor with an unprecedented mode of binding in the switch‐II allosteric pocket. This is the outcome of a computationally driven workflow based on the enumeration of novel chemical matter and stepwise prioritization. The most promising compounds were synthesized, biochemically tested, and co‐crystallized with KRAS G12C .